The Influence of Green Performance Appraisal and Green Compensation to Improve Employee Performance through OCBE - Ardiza, Fathia; Nawangsari, Lenny C.; Sutawidjaya, Ahmad H. (International Review of Management and Marketing, 2021)
This study aims to determine the effect of Green Performance Appraisal, Green Performance Appraisal and Green Compensation and Organizational Citizenship Behavior for the Environment / OCBE on employee performance in 2 groups of employees based on employee length of service. This type of research is quantitative using a survey method with a sample of 76 people. Data analysis using SEM with the Smart PLS program. This study proves that OCBE does not mediate the effect of Green Compensation and Rewards and Green Performance Appraisal on Employee Performance in groups of employees who have worked for less than 5 years. Meanwhile, for groups of employees who have worked for more than 5 years, OCBE only mediates the effect of Green Compensation and Rewards on Employee Performance. Keywords : Green Performance Appraisal, Green Compensation and Reward, OCBE, Employee performance JEL Classifications: L2, J2 DOI: https://doi.org/10.32479/irmm.11632